The Role of Emotional Intelligence in Project Success, Mediated by the Management of Conflict, Communication and Trust - Cavaletti, Samir; Bizarrias, Flavio Santino; Penha, Renato; Silva, Luciano Ferreira da (International Journal of Business, Economics and Management, 2021)
Companies have widely used project management to face the fast-paced challenges of today’s business environment. In addition to the techniques and procedures available in this area of knowledge, personal skills have been growing as tools for project success. Emotional intelligence (EI) has been studied as a soft skill that is prominent as a research topic. Although, extant literature does not discuss how EI influences project success when team management aspects, such as relationship conflict management, communication management, and trust-building, are put into place. This study aimed to determine how emotional intelligence influences the success of projects and under the mediating effect of these team management aspects. A quantitative survey was carried out, with data collected by survey (n=280) and analyzed through structural equation modeling and multiple regression analysis for the mediation’s effects, complemented by a latent class analysis to profile the emotional intelligence in the sample. The results showed that emotional intelligence positively influences project success mediated by executive actions of managing conflicts, communication, and trust. Three distinct emotional intelligence profiles were also observed, with significant differences between the extremes, concerning the studied constructs. As a contribution to this research, findings advance the understanding of the relationship between emotional intelligence and project success, which is conditioned by the executive actions of team management.